Evaluating the effects of emigration and remittances: A Costa Rican community in the face of restructuring class and gender hierarchies - Rodríguez, Leila (2016)
This article is based on a descriptive research project about the perception that residents of a rural Costa Rican town have about the effects of international migration on their community. Specifically, it examines the moral economy – the moral evaluation that current community members make in the face of the socioeconomic changes that emigration brings about. Based on qualitative interviews with non-migrants and return migrants, the results show that the most widely accepted migratory pattern is temporary, short-term, and that generates remittances that are invested in productive activities in the community. I conclude that the moral economy developed reproduces the idealized script of an egalitarian rural community reproduced by the traditional family.